Theodosius Borowik’s Book of Miracles “Historia abo powieść zgodliwa…”: a Unitarian Account of the Miracles of the Icon of Our Lady of Zhyrovitse - Stukaitė, Viltė (Literatūra, 2024)
The article analyses the book of miracles ‘‘Historia abo powieść zgodliwa...” (Vilnius, 1622), compiled by Theodosius Borowik, as a means of forming the cult of the Zhyrovitse icon. The chronology, typology, and geography of the miracles of Our Lady of Zhyrovitse are analysed to discuss the expression of the icon cult in the Unitarian Church. The study reveals the transformation of a religious artefact of the Orthodox tradition – the icon of Our Lady of Zhyrovitse – into the object of the union of the Eastern and Western Churches. It provides new data on the functioning of this icon in the society of the Grand Duchy of Lithuania in the second half of the 16th and the early 17th century.
Keywords: Theodosius Borowik; Religious literature of the Grand Duchy of Lithuania; Uniates; he icon of Our Lady of Zyrowicz; miracles; miracles books